Fault Instability and Its Relation to Static Coulomb Failure Stress Change in the 2016 Mw 6.5 Pidie Jaya Earthquake, Aceh, Indonesia - Kusumawati, Dian; Sahara, David P.; Widiyantoro, Sri; Nugraha, Andri Dian; Muzli, Muzli; Imran, Iswandi; Puspito, Nanang T.; Zulfakriza, Zulfakriza (Frontiers in Earth Science, 2021)
Herein, we applied the fault instability criterion and integrated it with the static Coulomb stress change (ΔCFS) to infer the mechanism of the 2016 Mw 6.5 Pidie Jaya earthquake and its aftershock distribution. Several possible causative faults have been proposed; however, the existence of a nearby occurrence, the1967 mb 6.1 event, created obscurity. Hence, we applied the fault instability analysis to the Pidie Jaya earthquake: (1) to corroborate the Pidie Jaya causative fault analysis; (2) to analyze the correlation between ΔCFS distribution imparted by the mainshock and the fault instability of the reactivated fault planes derived from the focal solution of the Pidie Jaya aftershocks. We performed the fault instability analysis for two possible source faults: the Samalanga-Sipopok Fault and the newly-inferred Panteraja Fault. Although the maximum instability value of the Samalanga-Sipopok Fault is higher, the dip value of the Panteraja Fault coincides with its optimum instability. Therefore, we concluded that Panteraja was the causative fault plane. Furthermore, a link between the 1967 mb 6.1 event and the 2016 Mw 6.5 earthquake is discussed. To analyze the correlation between the fault instability and the ΔCFS, we resolved the ΔCFS of the Pidie Jaya mainshock on its aftershock planes and compared the ΔCFS results with the fault instability calculation on each aftershock plane. We discussed the possibility of conjugate failure as shown by the aftershock fault instability. Related to the ΔCFS and fault instability comparison, we found that not all the aftershocks have positive ΔCFSs, but their instability value is high. Thus, we suggest that the fault plane instability plays a role in events that do not occur in positive ΔCFS areas. Apart from these, we also showed that the off- Great Sumatran Fault (Panteraja and Samalanga-Sipopok Faults) are unstable in the Sumatra regional stress setting, thereby making it more susceptible to slip movement.